Pemanfaatan Game Edukasi Wordwall untuk Meningkatkan Proses Belajar Online - Asmadi Asmadi (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2022)
Learning mentoring by parents or guardians of students at home is considered difficult, such as mathematics, science, and English subjects. If the material is difficult and delivered with media that is difficult to understand, the students of the State Junior High School 1 Purwodadi are less enthusiastic when learning distance online. This can be caused by a lack of attention and a lack of interest from students to take part in ongoing learning. Junior high school students who are still young children prefer to play games rather than study even though they both use Android. The author uses educational games with Wordwall applications for a fun online learning process and has the aim of improving the ability and understanding of students easily. The results of this activity are very useful because they can provide additional insight and knowledge about easy and fun learning, foster enthusiasm and learning motivation for students at the State Junior High School 1 Purwodadi, Grobogan Regency, Central Java, Indonesia, helping teachers to provide media that students like, fun and accidental learning occurs in understanding the learning material taught by the teacher.